2016
DOI: 10.1080/1612197x.2016.1187654
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation through sport: Different contexts different meanings

Abstract: Research on the role of sport as a social integrative agent for migrants has provided equivocal results. The purpose of this study was to investigate the relation between ethnic-cultural identity and sport environmental factors. Young migrant male athletes from two different societal and sport contexts were studied: migrants from Eastern European countries living in Greece (n = 60) and from Latin America living in Spain (n = 60). Participants completed measures of ethnic and cultural identity, task-oriented mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
(26 reference statements)
3
16
0
1
Order By: Relevance
“…In contrast, a disempowering climate characterized by a performance climate and controlling coaching behavior was negatively related to multiculturalism attitudes. The results coincide with previous findings conducted with migrant populations that identified links between factors of the sport climate, and in particular mastery climate and autonomy supportive coaching, and ethnic-cultural identity in young migrant athletes (Elbe et al, 2016). Papaioannou, Zourbanos, Krommidas and Ampatzoglou (2012) argued for the beneficial influence of a mastery motivational climate for both the individuals and society.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
See 3 more Smart Citations
“…In contrast, a disempowering climate characterized by a performance climate and controlling coaching behavior was negatively related to multiculturalism attitudes. The results coincide with previous findings conducted with migrant populations that identified links between factors of the sport climate, and in particular mastery climate and autonomy supportive coaching, and ethnic-cultural identity in young migrant athletes (Elbe et al, 2016). Papaioannou, Zourbanos, Krommidas and Ampatzoglou (2012) argued for the beneficial influence of a mastery motivational climate for both the individuals and society.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…They found that team cohesion could negatively predict feelings of fringe and lack of interaction with members of the host culture. A similar study by Elbe et al (2016) found that the motivational climate and particularly mastery climate and autonomy support were linked to an adaptive integrative profile in male adolescent migrants.…”
Section: Sport and Acculturationmentioning
confidence: 77%
See 2 more Smart Citations
“…In the current study, we use the Swedish version of an EU funded longitudinal project called Children of Immigrants Longitudinal Survey in four countries (CILS4EU; Dollmann et al, 2014) to analyse longitudinal relations between organized sport participation and indicators of integration (e.g., problem behaviours and amount of Swedish friends). The Swedish part of CILS4EU was carried out over two years across three measurement points in schools all over Sweden.…”
Section: The Current Studymentioning
confidence: 99%